Nonrelative sliding gear mechanism based on function-oriented design of meshing line functions for parallel axes transmission - Zhen Chen; Huafeng Ding; Ming Zeng (Advances in Mechanical Engineering, 2018)
In this article, the design of a nonrelative sliding gear mechanism for parallel axes transmission is presented. First, the general meshing line functions were actively designed for the nonrelative sliding transmission between parallel axes. The parametric equations of contact curves on the driving and driven gears were deduced by the coordinate transformations of function-oriented design of meshing line functions. The meshing between two contact curves on driving and driven gears follows the principle of space curve meshing. Based on two types of motion equations of meshing points, the parametric equations of driving and driven tooth surfaces were deduced according to the helical motion along the calculated contact curves. According to the calculation equations, two pairs of numerical examples were designed and material prototype samples were fabricated to experimentally validate the kinematic performances. After the two types of meshing line motion functions for nonrelative sliding meshing for parallel axes transmission were analyzed, a tooth contact comparative analysis was carried out between the nonrelative sliding gears with uniform motion of meshing points and involute gears, exhibiting better performances. This article introduces a new design method of nonrelative sliding gear mechanism for parallel axes transmission based on function-oriented design of meshing line functions.